2005
DOI: 10.1007/s00406-005-0629-z
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of schizophrenia and major affective disorder as a function of age, in the presence of strong cohort effects

Abstract: It remains unclear whether age at onset for major psychiatric disorders is a useful marker of etiologic and genetic heterogeneity. The authors examined how heritability of schizophrenia and major affective disorders varied with age at onset. The sample was drawn from a large archival data set collected by Lionel Penrose, comprising 3,109 families with two or more members first hospitalized in Ontario between 1874 and 1944. The authors studied 1,295 sibships with schizophrenia (n = 487), major affective disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…When we conducted a separate analysis of male and female subjects, we found that this association was significant in females, while in males it reached a trend toward significant difference. Several lines of evidence support strong heritability of age at onset in schizophrenia 4042. Moreover, there is a plethora of studies linking SNPs to age of psychosis onset.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…When we conducted a separate analysis of male and female subjects, we found that this association was significant in females, while in males it reached a trend toward significant difference. Several lines of evidence support strong heritability of age at onset in schizophrenia 4042. Moreover, there is a plethora of studies linking SNPs to age of psychosis onset.…”
Section: Discussionmentioning
confidence: 98%
“…Several lines of evidence support strong heritability of age at onset in schizophrenia. 40 42 Moreover, there is a plethora of studies linking SNPs to age of psychosis onset. Although the majority of these studies show that the risk allele for schizophrenia is simultaneously associated with earlier age of psychosis onset, there is a considerable number of studies linking the risk polymorphic variant to later age of psychosis onset.…”
Section: Discussionmentioning
confidence: 99%
“…Heritability estimates for psychiatric disorders such as bipolar (85%), unipolar disorder (59%), alcoholism (50–60%), attention deficit hyperactivity disorder (ADHD; 76%), and schizophrenia (85%) [Anon, ; McGuffin et al, ; Faraone et al, ; Husted et al, ; Stacey et al, ; Rommelse et al, ; Hallmayer et al, ] are notably higher than for other complex diseases such as cancer and several measures of heart disease, which typically have heritability estimates less than 60% (25–57%) [Austin et al, ; Sluijter et al, ; Page et al, ]. Traditional statistical approaches to gene identification for psychiatric disorders have used genetic markers to identify genetic variants that are associated with disease.…”
Section: Complexities In Psychiatric Geneticsmentioning
confidence: 99%
“…A number of studies have investigated whether age at schizophrenia onset affects recurrence risks for relatives but have yielded data that are not entirely conclusive (4, 9, 38–41). However, one recent study with a large sample size reported a significant increase in risk for schizophrenia among siblings for each 10‐year decrease in the age of onset in their affected sibling (42). In addition, recent work focusing on families of individuals who developed onset of psychosis before 12 years of age (childhood‐onset schizophrenia) has shown a higher rate of schizophrenia spectrum disorders among first‐degree relatives of these individuals than among relatives of individuals with adult‐onset schizophrenia (21, 22).…”
Section: Characteristics Of the Affected Individualmentioning
confidence: 99%